Notes on digital precatization in times of pandemic: An approach to the OnlyFans network - Rosero Fuentes, Danilo (2022)
The deployment of forms of work linked to the platform economy constitutes a phenomenon prior to the pandemic. In the post-pandemic world, which must be an accelerated growing trend. Thus, questions arise about the forms and mechanisms of exploitation that characterize these new business models, which, although they can be classified as phenomena of digital precariousness, should not be reduced to the workplace, as they involve another type of subordination mechanisms, like gender oppression. Outlining some indications through the approach of the OnlyFans social network, this article positions the following: the forms of work linked to the platform economy configure the materialization of extractive operations that, from the use of data and algorithms, are founded and at the same time reinforce mechanisms of subordination and forms of production of subjectivity that transcend labor.